The Influence of Brand Equity on Customer Loyalty through the Satisfaction of Online Transportation Application Users : - Muhammad Risky Illahi; Rojuaniah Rojuaniah (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to examine the relationship between sales promotion, brand experience, customer perceived value, brand equity, customer trust, customer satisfaction and customer loyalty at users of the Maxim online transportation application. Methodology:  The data were collected through an online survey and examined using Structural Equation Modelling (SEM) with the Partial Least Squares (PLS) approach. The sample consisted of 158 respondents living in Jakarta, aged between 18 and 60 years, who had used the Maxim application. Results: The results show that sales promotion and brand experience have a positive influence on brand equity, while perceived value does not. Furthermore, brand equity positively affects customer trust, customer satisfaction, and customer loyalty. In addition, customer trust and customer satisfaction positively influence customer loyalty and mediate the relationship between brand equity and customer loyalty. Conclusions:  The findings show that the brand equity provided by Maxim can significantly influence customer trust, satisfaction, and loyalty. Then, sales promotion and brand equity can significanly influence brand equity. Limitations:  This study focuses only on Maxim users in Jakarta and examines satisfaction and trust as mediating variables, thus limiting the generalizability of the results and excluding other potential factors influencing customer loyalty Contribution: This study provides practical implications for companies to continuously maintain and enhance marketing strategies that strengthen brand equity in order to create sustainable customer loyalty.